Potensi Pengembangan Tanaman Lanskap Pada Kelompok Tani Gelora Bunga Kota Batu - Jeko, Heribertus; Setyabudi, Irawan; Akbar, Moch. Azkari Hisbulloh (TRANSFORM: Journal of Tropical Architecture and Sustainable Urban Science, 2024)
Landscape plants are plants that are used in the landscape and function both ecologically and visually. This research aims to identify the potential of landscape plants in the Gelora Bunga Farmers Group, Batu City, and design a development strategy. This research used a qualitative descriptive method and was conducted in Sidomulyo Village, Batu City, East Java. The research results show that members of the Gelora Bunga Farmers Group have actively participated in the development of landscape plants, which has significantly improved the economy of the Sidomulyo Village community. The potential includes strategic location, various types of ornamental plants, large number of plants, easy access to the location, as well as the beauty of Sidomulyo Village which is widely known. These findings emphasize the importance of appropriate development strategies to maximize this potential and support local economic sustainability through landscape plants.